1997
DOI: 10.1051/kmae:1997028
|View full text |Cite
|
Sign up to set email alerts
|

L'hybridation dans les populations naturelles de salmonidés dans le Sud-Ouest de l'Europe et en milieu expérimental

Abstract: RÉSUMÉL'hybridation interspécifique entre le saumon atlantique et la truite commune dans la nature a été mise en évidence dans différents pays d'Europe et au Canada. Une étude a été entreprise pour examiner son incidence dans des populations de salmonidés de certaines rivières des Asturies (nord de l'Espagne) et du sud-ouest de la France. Elle a été complétée par des expériences en milieu contrôlé pour déterminer les causes et les conditions de la disparition des barrières comportementales permettant le mainti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…For example, jacks will court females and fight among themselves for primary male status if large anadromous males become scarce (Allen et al 2007). Even precocious males may assume this role if other male life history types are absent (Hutchings and Myers 1985;Beall et al 1997;Martinez et al 2001). Thus, the potential genetic contribution rates of different male life history types is dynamic; it may increase or decrease depending upon its prevalence in a spawning population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, jacks will court females and fight among themselves for primary male status if large anadromous males become scarce (Allen et al 2007). Even precocious males may assume this role if other male life history types are absent (Hutchings and Myers 1985;Beall et al 1997;Martinez et al 2001). Thus, the potential genetic contribution rates of different male life history types is dynamic; it may increase or decrease depending upon its prevalence in a spawning population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such an event has frequently been described, here and elsewhere (Garcia de Leaniz & Verspoor 1989;Beall et al 1997;Ayllon et al 2004). Indeed, such an event has frequently been described, here and elsewhere (Garcia de Leaniz & Verspoor 1989;Beall et al 1997;Ayllon et al 2004).…”
Section: Discussionmentioning
confidence: 85%
“…However, several studies in experimental conditions (Hutchings & Myers 1985;Beall et al 1997;Martinez et al 2001) have shown that mature male parr could successfully mate alone with an anadromous female, without any courting stimulus. However, several studies in experimental conditions (Hutchings & Myers 1985;Beall et al 1997;Martinez et al 2001) have shown that mature male parr could successfully mate alone with an anadromous female, without any courting stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reasons stimulating hybridisation between these species include the reduction of the spawning areas in the regions of common occurrence, mainly caused by growing anthropogenic pressures (Elo et al., ), excessive fishery (Makhrov et al., ) and restitution of salmon in limited areas (Jansson and Öst, ). Hybrids of salmon and trout are also increasingly met in rivers where salmon populations exhibit a growing number of dwarf males, which seem to increase with decreasing abundance of the salmon population (Jansson et al., ; Elo et al., ) while showing an aggressive reproductive behaviour (Beall et al., ; Garcia‐Vazquez et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with correctly developed gonads comprise those that are able to generate an F2 generation and backcrossing (Chevassus, ; Falkowski et al., ). Previous investigation on the development of gonads in hybrids of salmon and trout have been based on the data collected from individuals representing an unknown or only a unidirectional hybridisation while also being based on a low number of samples (Chevassus, ; Crozier, ; Hurrell and Price, ; Jordan and Verspoor, ; Wilkins et al., ; Beall et al., ; Hedenskog et al., ). Some data were collected for the hybrids grown under culture conditions (Chevassus, ).…”
Section: Introductionmentioning
confidence: 99%